Am I A Fraud? Occurrence and Factors Associated with Impostor Phenomenon among Medical Students of Khartoum University, 2022. - Hamad, Hiba (International Journal of Medical Students, 2025)
BACKGROUND: The impostor phenomenon (IP) is the tendency to attribute success to external factors rather than to one’s abilities. It is frequent among medical students and has a negative impact on their wellbeing. . This study aimed to assess the occurrence and mental health factors associated with IP in medical students in Sudan. METHODS: A cross-sectional analytical study was conducted among University of Khartoum faculty of medicine students from December 2021 to January 2022, utilizing non-probability convenience sampling. The data collection tool employed was a Google form containing the Clance Impostor Phenomenon Scale (CIPS), Anxiety and depression were assessed using the Patient Health Questionnaire-4 (PHQ-4), burnout using the 2-item Maslach B burnout Inventory (MBI), and self-esteem with the Single-Item Self-Esteem Scale (SISE), with ethical clearance obtained from the department of community medicine at the faculty of medicine. Data was analyzed using SPSS version 26 with correlation analyses and Chi-square tests. RESULTS: In the study sample (n = 409), IP was found in 216 students (52.8%). Statistical association was found between IP and gender (p = 0.028) and academic year (0.008). A regression model found statistical association (p<0.001) between IP and self-esteem, parental over-protection, anxiety, depression, burnout, and perfectionism. Individual CIPS items corresponded with the total CIPS scores, and the responses to individual CIPS items differed based on gender. CONCLUSIONS: IP is frequent among University of Khartoum medical students and is linked to various family dynamics, personality traits, and mental health issues Efforts to increase awareness and facilitate IP management should be implemented.